High performance nonlinear adaptive control of temperature in cryogenic wind tunnel. (29th July 2019) - Zhu, Rusong; Wang, Hai; Yin, Guofu; Ding, Zhengtao
Summary: A new nonlinear adaptive control method based on Immersion and Invariant (I&I) approach is proposed for the temperature control of a cryogenic wind tunnel. The proposed control method can be applied to wide range temperature operation of the tunnel by incorporating the nonlinear dynamic model of temperature into the controller design. By constructing globally stable nonlinear observer, and rendering an invariant and attractive manifold in the state space of plant and observer, the uncertain gain of known disturbance and unknown wind tunnel wall temperature are considered in the same manner within the adaptive I&I control frame. In the design, nominal heat transfer coefficient is deployed to avoid complicated design process involving nonlinear parameterization. This design leads to an adaptive output feedback stabilization control law for the temperature with guaranteed transient and steady performance, which exhibits reasonable robustness to time delay in the control input channel and other uncertainties. The analysis and simulation show the effectiveness of the proposed control methodology.